Exploring First Nations Youth’s Strengths and School Engagement ... - Young, Jenna M. (Graduate Studies, 2016)
The present study examined the positive developmental factors of First Nations youth. Online surveys were administered to 18 First Nations youths to measure their developmental assets (i.e., personal, social, family, school, and community strengths), school engagement (i.e., behavioural, emotional, and cognitive), and cultural identity. Results reveal that middle school students demonstrate higher degrees of all variables measured compared to high school students. Findings also indicate that this sample of First Nations youths possess a relatively low amount of developmental assets. Furthermore, it was found that the more developmental assets this sample of First Nations youth possess, the more they are engaged at school. Lastly, results indicated that school engagement was not related to the First Nations youths’ cultural identity. Interpretations of these findings along with implications, limitations, and suggestions for future research are provided. Keywords: Indigenous youth, First Nations youth, ...